Comparison of clinical management of young and elderly asthmatics by respiratory specialists and general practitioners. (March 2015) - Tada, Mitsuhiro; Kuraki, Takashige; Taooka, Yasuyuki; Fuchita, Hiroshi; Karino, Fumi; Miura, Kiyotaka; Hamaguchi, Shunichi; Ohe, Miki; Sutani, Akihisa; Isobe, Takeshi
Abstract Background: Asthmatic death in the elderly is a serious problem worldwide. Differences in clinical skill between respiratory specialists (RS) and general practitioners (GP) are important in asthma control. The aim of this study was to compare asthma management between RS and GP. Methods: A cross-sectional survey was carried out in Shimane, Japan, in February 2009 using a questionnaire about patient background, treatment, asthma control test (ACT) and adherence to treatment. We secured the cooperation of 48 clinics (39 private clinics and 9 general hospitals). Asthmatics were divided into the elderly and young groups, and also into the RS and GP groups. Results: Clinical data of 779 patients were available for analysis. Elderly patients constituted 464 (RS group: 192, GP group: 272), while those of the young group were 315 (RS group: 207, GP group: 108). RS prescribed inhaled corticosteroids (ICSs) to their elderly and young patients more than GP. The total ACT score was higher in young RS group than in young GP group, but no such difference was noted in the elderly. Despite more asthma-related symptoms, the ACT showed that elderly GP asthmatics used fewer rescue inhalers than elderly RS. Self-assessment was higher in elderly GP than elderly RS asthmatics. Adherence to therapy was better in elderly patients than young patients. Conclusions: Elderly asthmatics treated by GPs underestimated the severity of their asthma and asthmatics seen by GPs were undertreated. The results stress the need to engage patients in educational activities, to adhere to guidelines, and to improve the coordination between GP and RS.